THE ROLE OF PHYSICAL EDUCATION IN THE EDUCATION OF STUDENTS TASHKENT INSTITUTE OF FINANCE (Spectrum Journal of Innovation, Reforms and Development, 2022)
Pupils' physical culture is an important factor determining the effectiveness of physical education. Also, physical culture is an integral part of the general culture of man and society.